Towards a Sharīʿah-Compliant Framework for AI-Supported Fatwa in Malaysian Hajj Management: A Maqāṣid al-Sharīʿah and Governance Perspective - Ab Razak, Mohamed Rashid Bin; Drs Nasrul, Muhammad Amrullah Bin; Abbas, Ibrahim (Millah: Journal of Religious Studies, 2026)
Malaysia is globally recognised for its comprehensive Hajj management system, spearheaded by Lembaga Tabung Haji (TH), which integrates financial, logistical, and spiritual preparation for pilgrims. With the growing interest in deploying artificial intelligence (AI) to provide real-time religious guidance, questions arise regarding the permissibility, reliability, and institutional implications of AI-supported fatwa delivery. In the Malaysian context, fatwa issuance remains a state prerogative vested in the Mufti and State Fatwa Committees, with binding effect only upon royal consent and gazettement, while national-level resolutions and Hajj-specific Muzakarah serve an advisory and operational role. This article aims to conceptualise a Sharīʿah-compliant and state-aligned framework for the use of AI as a supportive mechanism in fatwa delivery within Malaysian Hajj management, grounded in maqāṣid al-sharīʿah and existing fatwa governance structures. Employing a qualitative doctrinal approach, the study integrates analysis of uṣūl al-fiqh principles governing valid fatwa issuance, Malaysian legal–institutional arrangements, and recurrent Hajj-related issues documented in state fatāwā and Resolusi Muzakarah Haji Kebangsaan. It further evaluates the opportunities and epistemic risks associated with generative AI, including hallucinated rulings, jurisdictional confusion, and erosion of scholarly accountability. The analysis proposes a hybrid conceptual model in which AI functions strictly as a supportive tool rather than a substitute for human scholarship. The model emphasises retrieval-augmented generation grounded in curated and authenticated Malaysian fatwa corpora, clear differentiation between binding and advisory rulings, embedded evidentiary reasoning (istidlāl), escalation protocols to accredited muftīs, and institutional audit mechanisms. Framed through the higher objectives of Islamic law—particularly the protection of religion, life, intellect, dignity, and wealth—the proposed framework demonstrates that AI-supported fatwa delivery is normatively defensible only when tethered to state authority and governed by robust Sharīʿah and ethical safeguards. By aligning technological innovation with Malaysia’s established fatwa governance and maqāṣid-based ethics, this article contributes a context-sensitive blueprint for responsible AI integration in Hajj management, with potential relevance for other Muslim jurisdictions facing similar challenges.